Child and adolescent heart and lung post-transplant adherence - Melissa K. Cousino, PhD; Jill Plevinsky, PhD; Kristin Niel, PhD; Emma Rothman; Lauren M. Schnieder, PsyD; Kelly R. Wolfe, PhD, ABPP-CN; Michael O. Killian, PhD, MSW (JHLT Open)
Although adherence to the prescribed post-transplant regimen is critical to both graft and patient survival following thoracic transplantation, sub-optimal adherence is common among pediatric transplant recipients. Challenges specific to adherence contribute to higher rates of mortality among adolescent and young adult transplant recipients. Multi-directional individual-, family-, community-, system- and society-level factors contribute to one’s self-management skills and treatment adherence. This topical, expert-derived review provides an up-to-date overview of the pediatric thoracic transplant adherence literature with particular attention paid to actionable clinical, research, and policy efforts to enhance treatment adherence among pediatric thoracic transplant recipients, and ultimately, improve graft and quality of life outcomes.